Perancangan Sistem Informasi Pengelolaan Uang Kas Berbasis Website Pada Tanah Kas Adat Kelurahan Dusun Kebun - Nurkhofipah Nurkhofipah; Ahmad Nasukha; Bastomi Baharsyah (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2026)
Cash management in Tanah Kas Adat (TKA) is often constrained by manual recording processes that reduce efficiency and transparency. This study aims to design and implement a web-based Cash Management Information System to enhance financial accountability and operational effectiveness. The system was developed using the Waterfall method and modeled with Unified Modeling Language (UML). Laravel framework and MySQL database were utilized for system implementation. System testing was conducted using Black Box Testing and Load Testing through Loader.io. The results indicate that all features function properly, with an average response time of 2060 ms and no server or client errors detected. User satisfaction evaluation yielded a score of 81.2%, indicating that the system is feasible and well accepted. Practically, the implementation of this system contributes to improved financial transparency, transaction traceability, and more efficient financial reporting within the Tanah Kas Adat management environment.